W.M. S. Thorington, The Code of Ordinances of the City Council of Montgomery 223, § 509 (1888) - (:unkn) unknown (My University, 1888)
Any person who uses fire arms of any kind while fighting in the streets, or other public place, (except in self defense or in the execution of law), must, on conviction, be fined not less than one nor more than one hundred dollars.
Keywords: DUELING